Breakthrough in polyurethane bio-recycling: An efficient laccase-mediated system for the degradation of different types of polyurethanes. (1st August 2021) - Magnin, Audrey; Entzmann, Lisa; Pollet, Eric; Avérous, Luc
Graphical abstract: Text: Enzymatic depolymerization of poly(ether-urethane foams). Highlights: A new step toward the biological recycling of polyurethanes. Laccase mediated system relevant for degradation of different polyurethanes. First demonstration of the enzymatic degradation of poly(ether urethane) (foam). Development of an analytical set to evaluate the enzymatic degradation of PU foams. Abstract: Development of green, efficient and profitable recycling processes for plastic material will contribute to reduce the expanding plastic pollution and microplastics accumulation in the environment. Polyurethanes (PU) are versatile polymers with a large range of chemical compositions and structures. This variability increases the complexity of PU waste management. Biological recycling researchers have recently demonstrated great interest in polyethylene terephthalate. The adaptation of this route towards producing polyurethanes requires the discovery of enzymes that are able to depolymerize a large variety of PU. A laccase mediated system (LMS) was tested on four representative PU models, with different structures (foams and thermoplastics), and chemical compositions (polyester- and polyether-based PU). Size exclusion chromatography was performed on the thermoplastics and this revealed a significant reduction in the molar masses after 18 days of incubation at 37 °C. Degradation of foams under the same conditions was demonstrated by microscopy and compression assay for both polyester- and polyether-based PU. This study represents a major breakthrough in PU degradation, as it is the first time that enzymatic degradation has been clearly demonstrated on a polyether-based PU foam. This work is a step forward in the development of a sustainable recycling pathway, adapted to a large variety of PU materials.